Impacts of projected climate change on sediment yield and dredging costs. Issue 9 (10th April 2018) - Dahl, Travis A.; Kendall, Anthony D.; Hyndman, David W.
Abstract: Changes in climate may significantly affect how sediment moves through watersheds into harbours and channels that are dredged for navigation or flood control. Here, we applied a hydrologic model driven by a large suite of climate change scenarios to simulate both historical and future sediment yield and transport in two large, adjacent watersheds in the Great Lakes region. Using historical dredging expenditure data from the U.S. Army Corps of Engineers, we then developed a pair of statistical models that link sediment discharge from each river to dredging costs at the watershed outlet. Although both watersheds show similar slight decreases in streamflow and sediment yield in the near‐term, by Mid‐Century, they diverge substantially. Dredging costs are projected to change in opposite directions for the two watersheds; we estimate that future dredging costs will decline in the St. Joseph River by 8–16% by Mid‐Century but increase by 1–6% in the Maumee River. Our results show that the impacts of climate change on sediment yield and dredging may vary significantly by watershed even within a region and that agricultural practices will play a large role in determining future streamflow and sediment loads. We also show that there are large variations in responses across climate projections that cause significant uncertainty in sediment and dredging projections.